ANALISIS BREAK EVENT POINT (BEP) SEBAGAI PENUNJANG KEBERHASILAN BAURAN PEMASARAN PADA UMKM GILINGAN BAKSO MARELAN - Wijaya, M. Rizky; Yusuf, Mona Friliani (Jurnal Daya Saing, 2025)
This study aims to analyze the role of Break Even Point (BEP) in supporting the success of the marketing mix in UMKM Gilingan Bakso Marelan. BEP is one of the financial analysis tools used to determine the minimum amount of sales that must be achieved so that income is balanced with costs, without experiencing losses or profits. In the context of UMKM, understanding BEP can be an important strategy to support decision making in the marketing mix, which includes products, prices, promotions, and distribution. This study uses a quantitative descriptive method with primary and secondary data obtained from observations, interviews, and related UMKM financial documents. The results of the study indicate that accurate BEP calculations help UMKM Gilingan Bakso Marelan in determining competitive selling prices, designing effective promotional strategies, and optimizing resource allocation for product distribution. Thus, BEP is an important financial indicator to support marketing mix management and increase business success.